Pengaruh Struktur Modal, Corporate Governance, dan Ukuran Perusahaan terhadap Kinerja Perusahaan Sektor Aneka Industri di BEI Periode 2015-2019he effect of Capital Structure, Corporate Governance and Firm Size on Firm Performance in Various Industrial Sector Companies listed on IDX 2015-2019 - Andiny, Dhela Widy; Hartono, Ulil (Jurnal Ilmu Manajemen, 2022)
The company's performance results from the company's activity that becomes the benchmark of the company's success. The purpose of this study is the effect of capital structure, corporate governance, and company size on company performance in multi-industrial Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. This research is included in the type of quantitative research. Return On Equity (ROE) in this study is used to measure company performance. The population in this study were 53 companies, and the samples obtained in the purposive sampling were 12 companies. The analysis technique in this study uses multiple linear regression. This study finds that capital structure, institutional ownership, board of commissioners and firm size do not affect firm performance. Thus, the company should pay more attention to the problems that will occur within the company so as not to hamper the company's performance. This study shows that managerial ownership affects company performance because the greater the number of managerial ownership in the company can reduce agency problems to improve company performance.